1983
DOI: 10.1037/0033-2909.93.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual rhythm in sensory processes: A review of fluctuations in vision, olfaction, audition, taste, and touch.

Abstract: Research showing menstrual changes in basic processes in five sensory modalities is reviewed and discussed. Although substantial variations of stimulus conditions and procedures make generalizations difficult, both visual and olfactory thresholds in women appear to be lower around the time of ovulation. Sensitivity to painful stimuli has generally been found to be lower in the premenstrual phase of the cycle. Auditory performance, less extensively investigated, has shown two peaks throughout the cycle, one aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
1
4

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 42 publications
(67 reference statements)
1
45
1
4
Order By: Relevance
“…A lower olfactory threshold was associated with the period of ovulation (22,23), while the thermal cold perception threshold appeared to be lower at the late follicular and midluteal phase compared with the early follicular phase (24). A higher pain threshold was documented during the middle follicular phase (25).…”
mentioning
confidence: 90%
“…A lower olfactory threshold was associated with the period of ovulation (22,23), while the thermal cold perception threshold appeared to be lower at the late follicular and midluteal phase compared with the early follicular phase (24). A higher pain threshold was documented during the middle follicular phase (25).…”
mentioning
confidence: 90%
“…This was vital to deal with adequately as several studies have revealed differences among men and women (35)(36)(37)(38). Some studies have shown the significant role of gender in the relationship between depression and loneliness.…”
Section: Impact Of Gendermentioning
confidence: 99%
“…This would enable more certain conclusions about the roles of estrogen and progesterone to be drawn. Control groups consisting of males, females using oral contraceptives, or post-menopausal females may be appropriate; this issue is discussed in a review by Parlee (1983).…”
Section: Mechanisms Of Gustatory-endocrine Interactionmentioning
confidence: 99%